Epigenetic silencing of TET1 mediated hydroxymethylation of base excision repair pathway during lung carcinogenesis. (1st January 2021) - Chen, Hong-qiang; Chen, Dong-jiao; Li, Yan; Yuan, Wen-bo; Fan, Jun; Zhang, Zhe; Han, Fei; Jiang, Xiao; Chen, Jian-ping; Wang, Dan-dan; Cao, Jia; Liu, Jin-yi; et al.
Abstract: The methylcytosine dioxygenase Ten-eleven translocation 1 (TET1) is an important regulator for the balance of DNA methylation and hydroxymethylation through various pathways. Increasing evidence has suggested that TET1 probably involved in DNA methylation and demethylation dysregulation during chemical carcinogenesis. However, the role and mechanism of TET1 during lung cancer remains unclear. In this study, we found that TET1 expression was significantly down-regulated and the methylation level was significantly up-regulated in 3-methylcholanthrene (3-MCA) induced cell malignant transformation model, rat chemical carcinogenesis model, and human lung cancer tissues. Demethylation experiment further confirmed that DNA methylation negatively regulated TET1 gene expression. TET1 overexpression inhibited cell proliferation, migration and invasion in vitro and in vivo, while knockdown of TET1 resulted in an opposite phenotype. DNA hydroxymethylation level in the promoter region of base excision repair (BER) pathway key genes XRCC1, OGG1, APEX1 significantly decreased and the degree of methylation gradually increased in malignant transformed cells. After differential expression of TET1, the level of hydroxymethylation, methylation and expression of these genes also changed significantly. Furthermore, TET1 binds to XRCC1, OGG1, and APEX1 to maintain them hydroxymethylated. Blockade of BER pathway key gene alone or in combination significantly diminished the effect of TET1. Our study demonstrated for the first time that TET1 expression is regulated by DNA methylation and TET1-mediated hydroxymethylation regulates BER pathway to inhibit the proliferation, migration and invasion during 3-MCA-induced lung carcinogenesis. These results suggested that TET1 gene can be a potential biomarker and therapy target for lung cancer. Graphical abstract: Image 1 Highlights: TET1 was significantly down-regulated in 3-MCA-induced lung carcinogenesis. DNA methylation regulated TET1 expression during 3-MCA-induced lung carcinogenesis. TET1 inhibited cell growth and metastasis of lung cancer in vitro and in vivo. TET1 act as a novel tumor suppressor in lung cancer. TET1 regulated hydroxymethylation and methylation of BER pathway key genes.